1978
DOI: 10.1152/jappl.1978.45.3.425
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen depletion in exercising rats infused with glucose, lactate, or pyruvate

Abstract: The influence of an intravenous infusion of glucose, lactate, or pyruvate on the work capacity and rates of glycogen depletion in the liver and hindlimb skeletal muscles of rats has been studied. Running time to exhaustion at a speed of 21 m/min on a treadmill at a +10 degrees incline was prolonged by glucose infusion but shortened by lactate or pyruvate infusions. Blood glucose concentrations were only lowered in the terminal stages of the exercise, whereas at this point lactate was elevated. Declines in live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…These authors concluded that net glycogen degradation during intermittent exercise could be reduced by up to 20% with CHO ingestion. This view was also supported by later workers (Ehrenstein et al 1970;Bagby et al 1978;Coyle et al 1983) However, some scientists in the 1980's, showed that CHO ingestion during exercise had no effect on rates of muscle glycogen utilisation (Fielding et al 1985;Coyle et al 1986;Flynn et al 1987;Hargreaves & Briggs 1988;Noakes et al 1988b;Mitchell et al 1989), while others demonstrated a sparing of muscle glycogen when CHO's were ingested during exercise (Bjorkman et al 1984;Hargreaves et al 1984;Erickson et al 1987;Simard et al 1988;Brouns et al 1989). The question of whether water or CHO replacement should be emphasised during prolonged exercise received a large amount of attention in the mid to late 1980s when commercial interests sponsored this type of research.…”
Section: Carbohydrate Ingestion and Exercise Performancesupporting
confidence: 74%
See 1 more Smart Citation
“…These authors concluded that net glycogen degradation during intermittent exercise could be reduced by up to 20% with CHO ingestion. This view was also supported by later workers (Ehrenstein et al 1970;Bagby et al 1978;Coyle et al 1983) However, some scientists in the 1980's, showed that CHO ingestion during exercise had no effect on rates of muscle glycogen utilisation (Fielding et al 1985;Coyle et al 1986;Flynn et al 1987;Hargreaves & Briggs 1988;Noakes et al 1988b;Mitchell et al 1989), while others demonstrated a sparing of muscle glycogen when CHO's were ingested during exercise (Bjorkman et al 1984;Hargreaves et al 1984;Erickson et al 1987;Simard et al 1988;Brouns et al 1989). The question of whether water or CHO replacement should be emphasised during prolonged exercise received a large amount of attention in the mid to late 1980s when commercial interests sponsored this type of research.…”
Section: Carbohydrate Ingestion and Exercise Performancesupporting
confidence: 74%
“…Over the past 30 years there has been evidence both for and against muscle glycogen sparing when ingesting CHO while exercising (Ahlberg et al 1967b;Bergstrom and Hultman 1967;Hultman 1967;Ehrenstein et al 1970;Bagby et al 1978;Bjorkman et al 1984;Hargreaves et al 1984;Fielding et al 1985;Coyle et al 1986;Flynn et al 1987;Erickson et al 1987;Hargreaves & Briggs 1988;Simard et al 1988;Brouns et al 1989;Noakes et al 1988;Mitchell et al 1989). However, Coggan and Coyle (1991) concluded that CHO ingestion while cycling at moderate-intensity (70-75% of V02max) does not reduce the rate of muscle glycogen utilisation.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic gluconeogenesis (John-Alder et al, 1986) and especially increased rates of glycogenolysis (Bagby et al, 1978) are essential to sustain prolonged submaximal locomotor activity in rats. Even when faced with an exogenous glucose infusion [final concentration 25% (w/w)], both trained and untrained rats experience significant hepatic glycogenolysis during exercise (Azevedo et al, 1998).…”
Section: Glycogen Concentration and Circadian Patternsmentioning
confidence: 99%
“…In other studies, carbohydrate supplementation has been shown to increase the amount of work that can be performed [3][4][5] as well as increase the duration of aerobic exercises [6,7]. The elevation of blood glucose, found in the laboratory test, can be associated with improved aerobic performance through the reduction of muscle glycogen use [7,27,28] or through the use of blood glucose as a predominant fuel source as glycogen becomes depleted [4,9,11].…”
Section: Discussionmentioning
confidence: 99%